Rancang Bangun Alat Simulasi Wiper Otomatis Berbasis Microcontroller Sebagai Media Pembelajaran Wiper Electrical System Alat Berat - Abd. Halim; Abdul Muis; Abdul Halik; Muhammad Saiful (Politeknik Negeri Samarinda, 2020)
A wiper is a device used to clean rainwater and particles from glass that can block the vision of heavy equipment operators during rainy weather. To clean rainwater from the glass, the operator must activate the wiper switch. When the operator is focused on work often the operator forgets to turn on the windshield wipers or turns off the windshield wipers, it can disturb the operator's concentration especially on the machine when working. Automatic wipers are devices that detect rainwater with the help of a raindrop sensor FC 37 to activate the wiper motor without the need to activate the switch. With this automatic wiper the operator can comfortably work when the weather is rainy. The purpose of making a microcontroller arduino ino R3 based automatic wiper simulation tool is as a learning media for wiper electrical system applications on heavy equipment. The results obtained from simulation testing based on the standard operating procedures that have been made and successfully work well without problems.